High-Affinity Interaction between Fibronectin and the Group B Streptococcal C5a Peptidase Is Unaffected by a Naturally Occurring Four-Amino-Acid Deletion That Eliminates Peptidase Activity - Tamura, Glen S. (American Society for Microbiology (ASM), 2006)
The streptococcal C5a peptidase (ScpB) of group B streptococci (GBS) is found in virtually all clinical GBS isolates and is required for mucosal colonization in a neonatal mouse model. ScpB inhibits neutrophil chemotaxis by enzymatically cleaving the complement component C5a. We previously identified a second function of ScpB as a fibronectin (Fn) adhesin using phage display. However, phage display can identify low-affinity interactions. We therefore measured the affinity of both full-length recombinant ScpB (FL-ScpB) and the 110-amino-acid phage display fragment (Scp-PDF) for immobilized Fn using surface plasmon resonance. The affinity for Fn was very high for both FL-ScpB (equilibrium dissociation constant [K(D)] = 4.0 nM) and Scp-PDF (K(D) = 4.4 nM) and is consistent with a biologically significant role for the adhesin activity of ScpB. We also studied the Fn adhesin activity of a common natural variant of ScpB (ScpBΔ) that contains a 4-amino-acid deletion that eliminates peptidase activity. The integrity of scpB is otherwise maintained, suggesting that the Fn adhesin activity of ScpB may be responsible for its conservation in these strains. The affinities of both FL-ScpBΔ (K(D) = 2.4 nM) and ScpBΔ-PDF (K(D) = 1.4 nM) for Fn are unaffected by the deletion. Complementation in trans by both scpB and scpBΔ corrected the Fn-binding defect of an scpB deletion mutant GBS strain to an identical degree. The high affinity of ScpB for Fn and the maintenance of this affinity in ScpBΔ support our hypothesis that the Fn adhesin activity of scpB plays a role in virulence.